Robo3A and Robo3B expression is regulated via alternative promoters and mRNA stability. Issue 1 (December 2016) - Ruedel, Anke; Schott, Mandy; Schubert, Thomas; Bosserhoff, Anja
Abstract Background The transmembrane receptor family Roundabout (Robo) was described to have an essential role in the developing nervous system. Recent studies demonstrated that Robo3 shows an altered expression in rheumatoid arthritis as well as in melanoma. Context and purpose of the study Until today no detailed studies of the two Robo3 isoforms (Robo3A and Robo3B) and their roles in rheumatoid arthritis synovial fibroblasts, respectively malignant melanoma are available. To get a better understanding regarding the role of Robo3A and Robo3B in the molecular process of rheumatoid arthritis and melanoma the exact characterization of expression and regulation is object of this study. Results mRNA and protein expression of the transcriptional variants were analyzed by quantitative RT-PCR respectively western blotting and revealed particularly enhanced expression of Robo3B in rheumatoid arthritis and melanoma. Promoter assays and inhibitor studies also disclosed that there is apparently a cell- and isoform-specific regulation of the Robo3 expression. Finally, dissimilar mRNA stabilities of Robo3A and Robo3B are identified as decisive posttranscriptional gene expression control. Conclusion In summary, this study supported an isotype specific role of Robo3B in disease hinting to different functional roles of each isoform.